Pharmacological properties of Annona muricata as an alternative therapy in cancer treatment: Systematic review - Obregón-La Rosa, Antonio José (2024)
[Objective] The objective was to determine the pharmacological and therapeutic properties of Annona muricata as an alternative or preventive therapy for cancer treatment. [Methodology] A systematic search was conducted in 3 databases (Scopus, Pubmed/MEDLINE, and Web of Science) using keywords and controlled vocabularies on Annona muricata, alternative or preventive therapy, and cancer treatment, following the methodology of the PRISMA statement. After the initial search, selected studies were exported to Mendeley as the bibliographic reference manager. Excel and a reference form were used for data extraction of the included studies. [Results] Ten studies were selected, which evidenced the pharmacological effect of Annona muricata leaf extracts on various cancer cells. All the selected studies corresponded to in vitro/in vivo assays. In addition, the studies demonstrated the presence of several bioactive compounds present in Annona muricata, which confer cytotoxic and anticarcinogenic power. [Conclusions] This systematic review showed that Annona muricata is a plant with excellent anticancer and cytotoxic potential to be used as an alternative or complementary therapy in various types of cancer because it has bioactive compounds such as acetogenins, phenolic compounds, flavonoids, and alkaloids, whose main effect is the apoptosis of cancer cells. However, further studies, mainly intervention studies, are required to prove its effectiveness to benefit human health.